Directing visual attention during action observation modulates corticospinal excitability. - David J Wright; Greg Wood; Zoe C Franklin; Ben Marshall; Martin Riach; Paul S Holmes (PLoS ONE, 2018)
Transcranial magnetic stimulation (TMS) research has shown that corticospinal excitability is facilitated during the observation of human movement. However, the relationship between corticospinal excitability and participants' visual attention during action observation is rarely considered. Nineteen participants took part in four conditions: (i) a static hand condition, involving observation of a right hand holding a ball between the thumb and index finger; (ii) a free observation condition, involving observation of the ball being pinched between thumb and index finger; and (iii and iv) finger-focused and ball-focused conditions, involving observation of the same ball pinch action with instructions to focus visual attention on either the index finger or the ball. Single-pulse TMS was delivered to the left motor cortex and motor evoked potentials (MEPs) were recorded from the first dorsal interosseous (FDI) and abductor digiti minimi muscles of the right hand. Eye movements were recorded simultaneously throughout each condition. The ball-focused condition produced MEPs of significantly larger amplitude in the FDI muscle, compared to the free observation or static hand conditions. Furthermore, regression analysis indicated that the number of fixations on the ball was a significant predictor of MEP amplitude in the ball-focused condition. These results have important implications for the design and delivery of action observation interventions in motor (re)learning settings. Specifically, providing viewing instructions that direct participants to focus visual attention on task-relevant objects affected by the observed movement promotes activity in the motor system in a more optimal manner than free observation or no instructions.